2019
DOI: 10.1002/ece3.5235
|View full text |Cite
|
Sign up to set email alerts
|

Amplicon sequencing of 42 nuclear loci supports directional gene flow between South Pacific populations of a hydrothermal vent limpet

Abstract: In the past few decades, population genetics and phylogeographic studies have improved our knowledge of connectivity and population demography in marine environments. Studies of deep‐sea hydrothermal vent populations have identified barriers to gene flow, hybrid zones, and demographic events, such as historical population expansions and contractions. These deep‐sea studies, however, used few loci, which limit the amount of information they provided for coalescent analysis and thus our ability to confidently te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(36 citation statements)
references
References 79 publications
8
28
0
Order By: Relevance
“…For instance, Thaler et al (2011) showed that the gastropod Ifremeria nautilei is genetically differentiated between the Manus and North-Fiji/Lau basins. Similar results have been reported in other species, such as the limpet Lepetodrilus schrolli (Plouviez et al, 2019), the shrimp Rimicaris variabilis and the squat lobster Munidopsis lauensis (Thaler et al, 2014). Moreover, this latter species is characterized by additional intrabasin structuring.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…For instance, Thaler et al (2011) showed that the gastropod Ifremeria nautilei is genetically differentiated between the Manus and North-Fiji/Lau basins. Similar results have been reported in other species, such as the limpet Lepetodrilus schrolli (Plouviez et al, 2019), the shrimp Rimicaris variabilis and the squat lobster Munidopsis lauensis (Thaler et al, 2014). Moreover, this latter species is characterized by additional intrabasin structuring.…”
Section: Introductionsupporting
confidence: 87%
“…schrolli (Plouviez et al, 2019) and A. boucheti (Breusing et al, 2021). Similarly to I. nautilei, L. schrolli is considered to possess lecithotrophic larvae (Berg, 1985;Craddock et al, 1997;Tyler et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…schrolli and squat lobster Munidopsis lauensis are probable lecithotrophic developers [see 63,64] and show genetic differentiation between Manus and Lau Basins (L. aff. schrolli) [10] or within Manus Basin (M. lauensis) [15]. This is not necessarily attributable to the general trend for marine invertebrates with lecithotrophic larvae to have shorter pelagic durations than planktotrophs [45,65].…”
Section: Discussionmentioning
confidence: 95%
“…The Southwest Pacific has been recognized as a single biogeographic province for deep-sea hydrothermal vent fauna based on its species composition [7,8]. Population connectivity of the component species has been well researched and documented among Manus (3˚S, 151˚E), North Fiji (16˚S, 173˚E) and Lau Basins (20˚S, 176˚E) (Fig 1) [9,10]. Different degrees of genetic connectivity have been shown for the vent-endemic species of mollusks and crustaceans in the three basins.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation